Clinical, Biological, and Laboratory Parameters as Predictors of Severity of Clinical Outcome and Response to Anti–TNF–Alpha Treatment in Ulcerative Colitis - Olsen, Trine; Florholmen, Jon (IntechOpen, 2011)
None